2014
DOI: 10.1080/09603123.2014.883593
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal clustering of isolated cleft lip with or without cleft palate in Poland

Abstract: We detect a strong signal of increased prevalence of isolated cleft lip with or without cleft palate in a single region of Poland, the Dolnośląskie voivodeship. Furthermore, we demonstrate a statistically significant prevalence differences between the urban and rural areas within this region. Through our comprehensive spatiotemporal analysis, we precisely define the cluster of the highest risk that comprises the eastern part of this voivodeship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…To provide additional protection against this type of bias, we reanalyzed the data using conditional logistic regression after 1:1 case–control matching based on confounding characteristics and did not observe any significant differences in the estimates of risk, further strengthening our internal validity. Lower education and rural residence at birth have also been associated with clefts in other studies (Messer et al, ; Lin et al, ; Materna‐Kiryluk et al, ). Second, even though we found no appreciable differences in our estimates of risk for any cleft type versus cleft lip with or without cleft palate, our limited sample size did not permit us to examine risk estimates for isolated cleft palate.…”
Section: Discussionmentioning
confidence: 63%
“…To provide additional protection against this type of bias, we reanalyzed the data using conditional logistic regression after 1:1 case–control matching based on confounding characteristics and did not observe any significant differences in the estimates of risk, further strengthening our internal validity. Lower education and rural residence at birth have also been associated with clefts in other studies (Messer et al, ; Lin et al, ; Materna‐Kiryluk et al, ). Second, even though we found no appreciable differences in our estimates of risk for any cleft type versus cleft lip with or without cleft palate, our limited sample size did not permit us to examine risk estimates for isolated cleft palate.…”
Section: Discussionmentioning
confidence: 63%
“…Rural-urban differences have been reported for many health and birth outcomes, 7 but few studies have investigated the relationship between rural maternal residence and OFC risk. [8][9][10][11][12][13] In all but one of these studies, infant OFC risk was higher for rural than for urban resident mothers. 12 Orofacial clefts risk has been reported to vary by race/ethnicity strongly enough to garner recommendations for studying aetiology separately for different racial/ethnic groups.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Only one study included data from Oklahoma, though it did not provide a detailed comparison of anomalies by race/ethnicity for Oklahoma children (Mai et al, ). Studies have identified spatial clusters of oral clefts in Texas (Cech, Burau, & Walston, ) and Poland (Materna‐Kiryluk et al, ); congenital heart defects in Wisconsin (Cronk, Gangnon, Cossette, McElroy, & Pelech, ), Maryland/District of Columbia (Kuehl & Loffredo, ), and China (Ma et al, ); and neural tube defects in China (Liao et al, ; Liao, Wang, Li, Guo, & Zheng, ).…”
Section: Introductionmentioning
confidence: 99%